PENERAPAN MODEL PROBLEM BASIC LEARNING DENGAN KEMAMPUAN REPRESENTASI EKSTERNAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK DI KELAS IXC SMP NEGERI 1 PELING TENGAH - Asmiaty Novitri (Jurnal Didaktika Pendidikan Dasar, 2019)
The research objective is to improve the students’ conceptual understanding of static electricity through the PBL model with external representation capabilities of class IXC in SMPN 1 Peling Tengah. This research is designed in classroom action research. The research steps consisted of planning,  implementation of actions,  observation, and reflection, conducted in two cycles. The results show that the students’ conceptual understanding is improved through PBL models with external representation abilities. The improvement could be seen from the teacher’s and students’ activity in the first cycle improved to 68% with a good category. While the students’ learning activities are improved in the first cycle to 62% include with a sufficient category. The teacher’s activity in the second cycle was improved to 95.9% with an excellent category. Whereas, the students’ activity in the second cycle was improved to 90% with a good category. The students’ learning outcomes improved to 82.6% in the first cycle and to 87.3 % in the second cycle. The students were able to express a problem with an ability to represent externally in the forms of images, graphics, verbal, tables, and mathematics, although they were still directed by the teacher